British Pronoun Use, Prescription, and Processing - Paterson, L. author. aut Link
X, 192 p.
Keywords: This study considers the use of they and he for generic reference in post-2000 written British English. The analysis is framed by a consideration of language-internal factors, such as syntactic agreement, and language-external factors, which include traditional grammatical prescriptivism and the language reforms resulting from second-wave feminism.